Historiografi Mahar dalam Pernikahan - Apriyanti Apriyanti (Pusat Studi Gender dan Anak Universitas Islam Negeri Raden fatah palembang, 2017)
The existence and position of women in classical times is very low and unlimited. The arrival of Islamic teachings brought by Rasulullah SAW has a mission that is developed is to elevate women. In the matter of inheritance, women who formerly had no part and even sick as heirs, began to get a share of inheritance. In the case of marriage too, where if a man wants to marry a woman then he must give something important from the dowry. Although the existence of a dowry is not a part of the pillars and conditions of marriage, but the dowry is a compulsory fee that must be filled by the husband. The noble purpose of this dowry price should always be monitored in order to avoid the things that will bring negative impact to the welfare of Muslims, especially for the woman as a candidate for the wife and the men as a husband candidate